Rancangan Distribusi Produk Batagor Kering Menggunakan Metode Distribution Requirement Planning Berdasarkan Bullwhip Effect Di PT XYZ - FADILLAH, MUHAMMAD ICHSAN; MUSTOFA, FIFI HERNI (e-Proceeding FTI, 2024)
PT XYZ is a distributor company for flour-based processed foods such as long dried batagor and square dried batagor products. The bullwhip effect causes company decisions in determining inventory levels to be inaccurate due to forecasting errors in anticipating demand variability. The purpose of this research is to plan distribution scheduling and minimize distribution costs for dried batagor. The Distribution Requirement Planning (DRP) method is expected to overcome the bullwhip effect by managing distribution for the coming period. Determining the order quantity in preparing the DRP table uses several lot sizing techniques including Lot For Lot (LFL), Economic Order Quantity (EOQ), Least Unit Cost (LUC), Least Total Cost (LTC). The results showed Least Total Cost (LTC) technique resulted in the smallest distribution costs for long dried batagor of IDR 9,925,412 and square dried batagor of IDR 7,178,813. Keyword: Dried Batagor, Bullwhip Effect, Distribution Requirement Planning, Lot Sizing. PT XYZ adalah perusahaan distributor olahan pangan berbasis tepung seperti produk batagor kering panjang dan batagor kering kotak. Bullwhip effect menyebabkan keputusan perusahaan dalam penentuan tingkat persediaan menjadi tidak akurat karena kesalahan peramalan dalam mengantisipasi variabilitas permintaan. Tujuan penelitian ini adalah merencanakan penjadwalan pendistribusian serta meminimasi biaya distribusi batagor kering. Metode Distribution Requirement Planning (DRP) diharapkan dapat mengatasi bullwhip effect dengan cara mengatur pendistribusian untuk periode yang akan datang. Penentuan kuantitas pemesanan dalam penyusunan tabel DRP menggunakan beberapa teknik lot sizing diantaranya Lot For Lot (LFL), Economic Order Quantity (EOQ), Least Unit Cost (LUC), Least Total Cost (LTC). Hasil penelitian menunjukkan teknik Least Total Cost (LTC) menghasilkan biaya distribusi terkecil untuk batagor kering panjang sebesar Rp9.925.412 dan batagor kering kotak sebesar Rp7.178.813. Kata Kunci: Batagor Kering, Bullwhip Effect, Distribution Requirement Planning, Lot Sizing.